Suicídio e povos indígenas brasileiros: revisão sistemática - de Souza, Ronaldo Santhiago Bonfim (Rev Panam Salud Publica, 2020)
OBJECTIVE. To describe the frequency, characteristics, and factors contributing to suicide in indigenous populations in Brazil. METHOD. A systematic review of the literature was performed in PubMed, SciELO, PsycINFO, and LILACS. All population-based studies focusing on suicide among indigenous populations in Brazil were included. RESULTS. The search identified 111 articles, of which nine met the inclusion criteria. Three of these studies were performed in the Midwest and four in the North of Brazil, while two covered all Brazilian regions. The ethnic groups investigated were specified in three studies (Terena, Kadiweu, Guato, Ofaie-Xavante, Guarani, Guarani-Kaiowá, and Guarani-Nandeva). Suicide rates were highest among males, single individuals, those with 4 to 11 years of schooling, and those aged 15 to 24 years. Suicides occurred most often in the home and on weekends, mostly by hanging. The main risk factors for suicide identified in the articles were poverty, historical and cultural factors, poor wellbeing indicators, family disintegration, social vulnerability, and lack of life or future perspective. CONCLUSIONS. All the studies indicated the need to engage communities in developing strategies, considering their cosmovision and the social, historic, and cultural view of each ethnic group to minimize risk factors and reduce suicide rates.